PENGARUH DAN ADMINISTRASI MANAJEMEN TERHADAP PENINGKATAN MUTU PENDIDIKAN - E. Syarifudin (Al Qalam, 1998)
The efforts for the enchancement of the educational quality cover, firstly, the administration which deter mines the principle goal of the policy, and, secondly, the management which concerns with the application to reach the said principle goal of the policy.The administrative management focuses on the tech nical policy which include planning, organizing, coor dinating and controlling, while the operative management focuses on the operation of the administra tion, personnel affairs, structure and infrastructure and public relations.